Distinct Routes to Understand the Relationship Between Dispositional Optimism and Life Satisfaction: Self-Control and Grit, Positive Affect, Gratitude, and Meaning in Life - Oriol, Xavier (2020)
Over the last years, understanding the implications of prospective thinking toward the future has become of increasing interest. This study aims to delve into the relation between dispositional optimism, one of the most relevant prospective constructs, and life satisfaction. Additionally, we also seek to prove the mediating effect of different cognitive and affective variables associated with both hedonic and eudaimonic well-being on this relationship. A first study is conducted with 275 secondary students to assess the relationship between optimism and life satisfaction through self-control and grit (14.82, SD = 1.07), which indicates a mediating effect of grit but not of self-control. A second study is carried out with 1,356 university students (21.5, SD = 2.35) to demonstrate the mediating effect of positive affect on dispositional optimism and life satisfaction. Results show a strong relationship between optimism and positive affect, but no mediating effect on life satisfaction. Finally, a third study comprising 371 secondary students (14.12, SD = 1.78) demonstrates the existence of a serial multiple mediation from gratitude and meaning in life over the relationship between optimism and life satisfaction. Implications are discussed in terms of how prospective variables like dispositional optimism may lead to an increase in subjective well-being (SWB) through different affective and cognitive mechanisms.